2011
DOI: 10.3892/ijmm.2011.743
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and expression of ATPase family AAA domain containing 3A, a novel anti-autophagy factor, in uterine cervical cancer

Abstract: Abstract. Our aim was to determine the association of human papillomavirus (HPV) infection with the expression of ATPase family AAA domain containing 3A (ATAD3A), an anti-autophagy factor, in uterine cervical cancer (UCC). The HPV genotype was determined by an Easychip HPV blot assay. ATAD3A expression was determined by immunohistochemical staining. High-risk HPV (hrHPV) was detected in 184 (88.9%) of 207 UCC cases. ATAD3A expression was detected in 164 (79.2%) UCC cases. A significant correlation was found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In this study, results demonstrated that ATAD3A expression was closely associated with BmNPV infection similar with a previously reported study on HPV infection (Fig. S2C)38. Interestingly, additional results demonstrated that overexpression of ATAD3A promotes virus multiplication in the Bombyx mori cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, results demonstrated that ATAD3A expression was closely associated with BmNPV infection similar with a previously reported study on HPV infection (Fig. S2C)38. Interestingly, additional results demonstrated that overexpression of ATAD3A promotes virus multiplication in the Bombyx mori cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…3). These results further explain why this protein expression correlates with virus infection and cancer in the mammalian cells3839. According to the phenomenon that propagation and replication of baculovirus would be inhibited through integrating silencing ATAD3A with the experimental results mentioned above, we speculate that virus could use ATAD3A to utilize host factor energy for their replication (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, ATAD3B is a putative marker which could enable the discrimination of oligodendroglioma from astrocytoma and surrounding healthy tissue (Hubstenberger et al 2008). More recently and confirming these results, it has been shown that ATAD3A constitutes an anti-apoptotic marker in lung tumors (Fang et al 2010) and a radioresistance marker in non-Hodgkin lymphoma and uterine cervical cancer (Jiang et al 2009;Chen et al 2011).…”
Section: P2mentioning
confidence: 64%
“…It is hypothesized that the HPV-host cell interaction stimulates the PI3K/Akt/mTOR pathway and inhibits autophagy, and in combination these events aid virus infection (36). In addition, persistent HPV infection may stabilize the ATPase family AAA domain containing 3A (an anti-autophagy factor) expression to inhibit cell autophagy and apoptosis, as well as increasing drug resistance in uterine cervical cancer (37). Simultaneously, the clinicopathological significance of negative Beclin-1 and LC3B expression in cervical SCC with hrHPV infection was investigated, and the results revealed that negative expression of Beclin-1 and LC3B in cervical SCC with hrHPV infection promoted a higher clinical TNM stage and lymph node metastasis, indicating that the absence of autophagy combined with hrHPV infection may accelerate cervical SCC progression.…”
Section: Discussionmentioning
confidence: 99%